Sex-specific phenotypes and metabolism-related gene expression in juvenile sticklebacks. (5th October 2017) - Velando, Alberto; Costa, María M; Kim, Sin-Yeon
Abstract : Lifestyle differences between males and females are linked to differences in metabolism, which appear from early stages of life. In the 3-spined stickleback, juveniles showed sexual differences in mitochondrial metabolism, maternally inherited organelles responsible for energy production, as evidenced by gene-expression profiles. We also found that juvenile females are darker and more fearful than males, and these phenotypic differences are related to sex-specific expression of metabolism genes. Abstract: To fully understand the evolution of sexual dimorphism, it is necessary to study how genetic and developmental systems function to generate sex-specific phenotype as well as sex-specific selection. Males and females show different patterns of energy storage and mitochondrial metabolism from early stages of life, and this may underlie sex-specific developmental pathway to shape both juvenile and adult phenotype. Here, we examined sex-specific relationships between juvenile morphology and behavior, and transcriptional profiles of 4 candidate genes related to mitochondrial function in the 3-spined stickleback. This study provides, for the first time to our knowledge, evidence for sex differences in melanin pigmentation and antipredator behavior as well as the expression of mitochondria-related genes in juvenile sticklebacks. Males were paler and bolder, and overexpressed genes involved in mitochondrial respiration and antioxidant enzymes compared to females. Relationships between phenotypic traits and gene expression were also sex-specific. In general, females showed stronger positive correlations between body size or pigmentation and the expression of genes involved in mitochondrial biogenesis and activity. In both sexes, more fearful individuals overexpressed those genes. Our results suggest that mitochondrial function may either facilitate or constrain sex-specific responses to selection on dimorphic phenotype, possibly generating intralocus sexual conflict on the transcriptional regulation of mito-nuclear genes during ontogeny. This study highlights that mitochondrial regulation plays an important role in the process of phenotypic differentiation between the 2 sexes from early stages of life before apparent sexual dimorphism appears.